ECOLOGICAL FUNCTION OF THE STATE AND PROBLEMS OF ITS REALIZATION IN MODERN CONDITIONS - Alexey A. Ryzhov (Russian Studies in Law and Politics)
The article deals with the environmental function of the state and the problems of its realisation in modern conditions. The study covers key aspects of the state environmental policy, including legal regulation, interaction with the private sector and civil society. Particular attention is paid to analysing the factors that hinder the effective implementation of the environmental function, such as lack of funding, imperfect law enforcement practices and contradictions between economic and environmental interests, which in turn negatively affects environmental security as a whole. The paper also offers recommendations for improving the implementation of the state’s environmental function, taking into account modern global challenges and trends in the transition to sustainable development. In the process of the research various opinions and approaches of many authors who have studied the topic of ecological function of the state have been analysed. The article also reflects different approaches to the definition of the essence of such legal category as ‘ecological function of the state’. It is proposed to use not only legal mechanisms for the implementation of environmental function, but also to use tax, sociological, economic tools that will make compliance with environmental legislation and minimisation of harmful impact on the environment a fashionable and economically beneficial activity. The variants and measures of realisation of ecological function are offered, introduction of which in practical activity will allow to improve quality of realisation of ecological function by the state that will positively reflect on ecological safety.